Formation of segmented fluid train and related microfluidic chip fabrication - Chan, Kin Wai. (2009)
The results of research works had been recorded inside this report. There were two different experiments scopes for these research works. The first scope was to determine liquid droplets were able to move inside specified channel and at desired speed without any problem. Thus, the actual important and expensive experiments were able to complete at desire timing without any problem and wastage. The first chapter testing was ink droplet able to move inside a channel without detaches into two or more droplets at high flow speed. The first idea was used oil inside the channel as lubricant. Second idea was applied Teflon on the surfaces of channel. Experiments results at chapter 1 show that ink droplet was able to move smoothly inside the channel without having any problem. Chapter 2 to 5 experiments were making use the results at chapter 1 to further investigate the characteristic of ink droplets when moving inside channel at desired flow speed. There were good results obtained in between chapter 2 and 5. The second scope was to determine how to stop liquid droplet at desire location. The first idea was making use pressure different inside the channel to stop ink droplet at desired location. Thus, a window opening was created above the channel. Therefore, when ink droplet pass through window opening the pressure at the back of ink droplet will drop to room pressure. Hence, there was no more forces to push ink droplet further and ink droplet will stop right after the window opening. But the actual finding of chapter 6 experiments were thin surface tension was created on window opening thus ink droplet didn’t stop at the desire location. Therefore, new ideas were implemented at chapter 7 and 8 in order to ensure ink droplet stopped at desired location. Chapter 7 results did provide a better control of ink droplet stopping position but ink droplet was not stopped at the location consistently. Chapter 8 results show that ink droplet was able to stop at desired location at certain configuration set up, flow rate, ink droplet size and window opening. However, it was limited to certain process parameter in order to the ink droplet. But, chapter 8 results did provide a better concept of stopping ink droplet at a location consistently, which was the size of ink droplet need to be smaller than the window opening. Chapter 9 results did prove that concept of having ink droplet smaller than the window opening were able to stop ink droplet at desire location.